Primary pulmonary mucosa-associated lymphoid tissue lymphoma with amyloid light chain-type amyloidosis - Shuta Ohara; Kenji Tomizawa; Shigeki Shimizu; Kenichi Suda; Toshio Fujino; Akira Hamada; Takamasa Koga; Masaya Nishino; Yoshihisa Kobayashi; Katsuaki Sato; Masato Chiba; Masaki Shimoji; et al. (Surgical Case Reports)
Abstract Background A total of 75% of patients with Sjögren’s syndrome are complicated with pulmonary lesions, of which 12% are lymphoma and 6% are amyloid nodules; the coexistence of both is considered to be rare. Case presentation A 67-year-old female with Sjögren’s syndrome presented with multiple pulmonary nodules on chest computed tomography. Since a definitive diagnosis by transbronchial biopsy was not obtained, wedge resection of the nodules was performed. Pathologic diagnosis revealed eosinophilic deposition that stained positive with Congo red. In addition, lymphoepithelial lesions and lymphocytic infiltration were observed. Lymphocytes with monoclonal proliferation predominantly had κ chain. Based on these findings, the nodules were diagnosed as mucosa-associated lymphoid tissue (MALT) lymphoma with amyloid deposition. Conclusions The combination of these diseases is very rare, and this is the sixth resected case to the best of our knowledge.